Infection and apparent invasion of Vero cells by Paracoccidioides brasiliensis - Mendes-Giannini, Maria José Soares [UNESP]; Ricci, L. C. [UNESP]; Uemura, M. A. [UNESP]; Toscano, E. [UNESP]; Arns, C. W. [UNESP] (My University, 1994)
Paracoccidioides brasiliensis probably uses many different mechanisms to establish itself in the host and cause disease. In this work, we assess an in vitro model system which uses cultured mammalian cells to investigate the virulence factors of P. brasiliensis. We were able to demonstrate an invasion process of the yeast form of this fungus in Vero cell cultures. We deduced that the overall invasive process involved three steps: adhesion, followed by invasion of individual epithelial cells and spread to adjacent cells.
Keywords: Cell culture; Epithelium cell; Fungus; Immunofluorescence; Immunoperoxidase staining; Nonhuman; Paracoccidioides brasiliensis; South american blastomycosis; Vero cell; Animal; Cell Adhesion; Cercopithecus aethiops; Models, Biological; Paracoccidioides; Paracoccidioidomycosis; Support, Non-U.S. Gov't; Time Factors; Vero Cells